The use of sticky ovitraps to estimate dispersal of Aedes aegypti in northeastern Mexico - Ordóñez González, José Genaro; Mercado Hernández, Roberto; Flores Suárez, Adriana Elizabeth; Fernández Salas, Ildefonso (American Mosquito Control Association, 2001)
A newly designed sticky ovitrap was used to determine the dispersal Right of the dengue vector Aedes aegypti in northeastern Mexico. Unfed marked females were released in the field where 100 sticky ovitraps had been positioned within a circular area 300 m in diameter. Success of this method was represented by a 7.7% (31 of 401) recapture rate during a 19-day sampling period. The maximum dispersal distance was 120 m with a mean of 30.5 m +/- 4.5 SD. Drastic hot and dry climatic conditions at the study site may have restricted mosquito dispersal. As expected, mostly gravid female mosquitoes were captured in the ovitraps. The method of sticky ovitraps proved to be useful and inexpensive for Ae. aegypti dispersal studies in Latin American countries. In addition to the marked mosquito populations, unmarked Ae. aegypti, Culex sp.. roaches, and even small vertebrates such as lizards and sparrows were found glued to the sticky ovitraps. Based on these studies, the use of sticky ovitraps is recommended for iie. aegypti dispersal studies, specially for dengue control programs in developing countries.